2010
DOI: 10.1111/j.1582-4934.2009.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

The actin filament cross‐linker L‐plastin confers resistance to TNF‐α in MCF‐7 breast cancer cells in a phosphorylation‐dependent manner

Abstract: We used a tumour necrosis factor (TNF)-α resistant breast adenocarcinoma MCF-7 cell line to investigate the involvement of the actin cytoskeleton in the mechanism of cell resistance to this cytokine. We found that TNF resistance correlates with the loss of cell epithelial properties and the gain of a mesenchymal phenotype, reminiscent of an epithelial-to-mesenchymal transition (EMT). Morphological changes were associated with a profound reorganization of the actin cytoskeleton and with a change in the repertoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
(53 reference statements)
1
33
0
Order By: Relevance
“…Because a correlation between the invasive capacity of melanoma cells and the phosphorylation state of L‐plastin on Ser5 has been suggested before (10), we continued by investigating L‐plastin Ser5 phosphorylation in the 4 breast cancer cell lines. To this end, we used an antibody specifically recognizing Ser5‐P‐LPL (anti‐Ser5‐ P antibody) raised and characterized by our group (3, 7, 14). Although the L‐plastin expression level is higher in the invasive compared with the noninvasive cell lines, our results clearly show high‐baseline L‐plastin Ser5 phosphorylation in the invasive cell lines BT‐20 and MDA‐MB‐435S as compared to absent or extremely weak phosphorylation in the noninvasive cell lines MCF7 and SK‐BR‐3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because a correlation between the invasive capacity of melanoma cells and the phosphorylation state of L‐plastin on Ser5 has been suggested before (10), we continued by investigating L‐plastin Ser5 phosphorylation in the 4 breast cancer cell lines. To this end, we used an antibody specifically recognizing Ser5‐P‐LPL (anti‐Ser5‐ P antibody) raised and characterized by our group (3, 7, 14). Although the L‐plastin expression level is higher in the invasive compared with the noninvasive cell lines, our results clearly show high‐baseline L‐plastin Ser5 phosphorylation in the invasive cell lines BT‐20 and MDA‐MB‐435S as compared to absent or extremely weak phosphorylation in the noninvasive cell lines MCF7 and SK‐BR‐3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PI3K has also been reported to play a role in L‐plastin phosphorylation in human neutrophils (13, 16), but not in T lymphocytes (18). Although an siRNA knockdown of PKCδ (3, 14) and PKCβ II (17) reduced L‐plastin Ser5 phosphorylation, it has to be taken into account that most reports are based on activation and/or inhibition studies. Strikingly, all inhibitors used to demonstrate the involvement of PKA and PKC (H89, GF109203X, Gö6976, and Ro‐31–8220) in L‐plastin phosphorylation also strongly inhibit RSK2 (47, 48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories are highly enriched in genes linked to cell adhesion, actin cytoskeleton dynamics and TGFβ-dependent induction of EMT. 22 While the autophagy gene function category appeared at rank #189 (p-value 3.24E-02) in the operon platform, it was the most regulated pathway in the dataset obtained with the autophagy-dedicated array (p-value 2.74E-14) (Sup. Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Then, 29 DEGs enriched in the category of actin cytoskeleton, while abnormity of structure or function of actin cytoskeleton is related to drug resistance of many cancers including breast cancer. Previous reports indicated that the molecular motor recruitment in the microtubule environment was associated with Taxol resistance of breast cancer (Froidevaux-Klipfel et al, 2011), and the actin filament cross-linker L-plastin was related to TNFalpha resistance in breast cancer (Janji et al, 2010). We speculated that actin cytoskeleton disorder might also play important roles in Lapatinib-resistance, but concrete mechanism is still worth further studying.…”
Section: Discussionmentioning
confidence: 91%